4.2k views
1 vote
(6h + 8) - (3h + 2) = 15
PLEASE HELP I ALSO NEED TO SHOW WORK

User Rakibtg
by
5.1k points

2 Answers

6 votes

Answer:

h=3

Explanation:

1 Remove parentheses.

6h+8-3h-2=156h+8−3h−2=15

2 Simplify 6h+8-3h-26h+8−3h−2 to 3h+63h+6.

3h+6=153h+6=15

3 Subtract 66 from both sides.

3h=15-63h=15−6

4 Simplify 15-615−6 to 99.

3h=93h=9

5 Divide both sides by 33.

h=\frac{9}{3}h=

​3

​9

​​

User Pandoragami
by
5.2k points
2 votes

Answer:


h=3

Explanation:

So we have the equation:


(6h+8)-(3h+2)=15

First, let's distribute the negative:


(6h+8)+(-3h-2)=15

Combine like terms:


(6h-3h)+(8-2)=15

Subtract or add:


3h+6=15

Subtract 6 from both sides:


3h=9

Divide both sides by 3:


h=3

And we're done!

User Ryan Watkins
by
4.5k points